Effect of Adenyl-Cyclase Activators, Phosphodiesterase Inhibitors and Pyridoxal-5-Phosphate on Platelet Aggregation and Adenosine-3’-5’-Cyclic Monophosphate Accumulation - Zahavi, M; Zahavi, J; Kakkar, V V (Thrombosis and Haemostasis, 1984)
The effect of prostaglandin E1 (PGE1) and compound BW245C, adenyl-cyclase activators, theophylline, papaverine and dipyridamole, phosphodiesterase (PDE) inhibitors and pyridoxal- 5-phosphate (PALP) on inhibition of platelet aggregation (PA) and platelet c-AMP accumulation was determined in human platelet-rich plasma (PRP) and washed platelets. PGE1 at 280 nM and BW245C at 7.7 nM induced a significant PA inhibition in PRP and washed platelets (though less pronounced by PGE1) concomitant to a very large increase (8-13-fold) in platelet cAMP level both in PRP and washed platelets. At comparable PA inhibition, c-AMP level was not significantly changed by PALP and only moderately (but significantly) increased (2-4.6-fold) by PDE inhibitors. PALP or theophylline potentiated both PGE1 induced platelet c-AMP accumulation and PA inhibition. Yet PALP potentiated theophylline-induced PA inhibition without affecting platelet c-AMP level.Our results indicate that 2 c-AMP pools are presumably present in the platelets, since at comparable c-AMP accumulation PDE inhibitors or BW245C were more effective than PGE1 in PA inhibition in PRP. Morever, this pattern was more pronounced in washed platelets and was also found in the presence of thrombin and adenosine diphosphate which induced a decrease in platelet c-AMP level. The effect of PALP on PA inhibition is presumably mediated by 2 mechanisms: a) a direct effect on the platelet membrane independent from the c-AMP system, b) In the presence of PGE1, the increment in PA inhibition, is through further indirect activation of the adenyl-cyclase. The mechanism of PA inhibition by BW245C in intact platelets, is most probably through activation of adenyl-cyclase. This study emphasize the importance of c-AMP accumulation in the inhibition of PA.
Keywords: c-AMP; Platelet aggregation inhibition; Pyridoxal-5-phos-phate; Compound BW245C